Detection of Fusobacterium nucleatum in Patients with Colitis-Associated Colorectal Cancer - Dregelies, Theresa; Haumaier, Franziska; Sterlacci, William; Backert, Steffen; Vieth, Michael (Current Microbiology, 2023)
Fusobacterium nucleatum is supposed to play a critical role in the development of colorectal cancer. The species has also been associated with ulcerative colitis (UC) that can progress into colorectal cancer, however, the involvement of bacteria in this process remains unclear. We analysed 177 colon biopsies obtained from patients during screening, including 20 healthy controls, 56 UC cases and 69 cases at different stages of progression to colitis-associated cancer (CAC); 32 samples of sporadic colorectal carcinoma (sCRC) were also included. The presence of F. nucleatum was detected by quantitative real-time PCR (qPCR). Our data show an association between the presence of the bacteria and the progression of carcinogenesis in UC patients. In 39.5% of CAC samples F. nucleatum was detected, compared to only 1.8% in UC cases. The bacteria were detected in 6.3% of samples with initial neoplastic transformation, so-called low-grade dysplasia (LGD), whereas high-grade dysplasia (HGD) resulted in 33.3% of samples positive for F. nucleatum. The fraction of F. nucleatum-positive samples from sCRC cases was 56.3%, which was not significantly different to the CAC group. We conclude that F. nucleatum is associated with the occurrence and progression of colon carcinogenesis, rather than with UC itself.
CRIS-Team Scopus Importer:2023-08-11

Frequency of Her2-low in colorectal cancer and its relations with the tumor microenvironment - Lang-Schwarz, Corinna; Vieth, Michael; Dregelies, Theresa; Sterlacci, William (Pathology Research and Practice, 2023)
Background: To date, little is known regarding human epithelial growth factor receptor (HER2) low-expressing colorectal cancer (CRC). Due to promising rising therapies with HER2-antibody-drug conjugates we aimed to analyze the frequency of HER2-low in patients with CRC. Additionally we characterized the clinicopathologic background of this group and its potential relationship with the tumor microenvironment represented by budding and tumor infiltrating lymphocytes (TILs). Methods: 319 patients with CRC, stages I–IV, were enrolled. HER2-immunohistochemistry (IHC) as well as fluorescence in situ hybridization (FISH) were performed on tissue microarrays. IHC was evaluated semiquantitatively and software-assisted using the HERACLES Diagnostic Criteria for CRC. HER2-low was defined as IHC 1 + or 2 +/FISH negative. HER2-IHC results were compared with budding, TILs and their combinations. Results: The HER2 low-expressing subset represented almost one half of all CRC (47.1 %). Assessment was highly reproducible with different methods. HER2-low cases were significantly more often lower T-, N-, and tumor stage and had less L1 compared with HER2-0. Additionally, they showed more often TILs > 5 % (p = 0.001). The difference between HER2-0 and HER2-low was highly significant between the four budding/TILs-groups (p < 0.001). Cases with low budding/high TILs were more often HER2-low. The highest difference was seen between the low budding/high TILs-group and the low budding/low TILs-group (p < 0.001). Conclusions: HER2-low expression in CRC is frequent and involves nearly one half of all patients. We could show a relationsship between HER2-low expression and the tumor microenvironment. Special attention should be paid to the low budding/high TILs group in future research.
CRIS-Team Scopus Importer:2023-03-31
Keywords: Budding; Colorectal cancer; Her2-low; TILs

Methylation Analysis of Colitis-Associated Colorectal Carcinomas. - Haumaier, Franziska; Dregelies, Theresa; Sterlacci, William; Atreya, Raja; Vieth, Michael (Discovery medicine, 2024)
BACKGROUND: Ulcerative colitis is a well-known inflammatory bowel disease. Patients have an increased risk of developing colitis associated carcinoma (CAC). It is important for patient management to be able to distinguish between ulcerative colitis associated carcinoma and sporadic carcinoma (sCRC). However, this distinction is frequently very challenging. It is not readily possible to differentiate this histologically. However, the diagnosis is crucial for the patient's further treatment and follow-up. An attempt was therefore made to develop a diagnostic regime that would enable a reliable distinction between sCRC and CAC. METHODS: We screened 96 patients analyzing more than 850,000 methylation hotspots, to detect distinct epigenetic patterns between both types of carcinomas. Patients with sporadic carcinoma and colitis-associated carcinoma as well as patients with normal colon and patients with confirmed ulcerative colitis without neoplasia were used for the analysis. By extensively filtering the results, methylation sites relevant to distinguish between CAC and sCRC were identified. RESULTS: After the results were filtered, three methylation sites relevant to distinguish between CAC and sCRC were identified. For this purpose, methylation limit values were defined, which favor the samples as CAC or sCRC up to a certain methylation value of the methylation sites. The combination of three methylation sites allows a correct assignment to CAC or sCRC in 94.5% of the cases. CONCLUSION: The results show that these three methylation sites are promising markers in the diagnosis of CAC vs sCRC. Nevertheless, the diagnosis should always be made in conjunction with histomorphological analyses.
EVALuna2:591089

Mutational analysis differentiating sporadic carcinomas from colitis-associated colorectal carcinomas - Dregelies, Theresa; Haumaier, Franziska; Sterlacci, William; Backert, Steffen; Vieth, Michael (Cell Communication and Signaling, 2024)
BACKGROUND: Ulcerative colitis (UC) is a chronic inflammatory bowel disease (IBD) that is associated with increased risk of developing colitis-associated carcinoma (CAC). The genetic profile of CACs is fairly similar to the sporadic colorectal carcinomas (sCRCs), although showing certain differences in the timing and sequence of alterations that contribute to carcinogenesis. Also, both cancer types typically show a strong histological resemblance, which complicates the pathologists' diagnosis. Due to the different clinical consequences, it is of utmost importance to categorize the corresponding cancer type correctly. METHODS: In this study, we determined the mutation profiles of 64 CACs and sCRCs in the hotspot regions of 50 cancer-associated genes and compared them to 29 controls to identify genetic gene variants that can facilitate the pathologists' diagnosis. Pearson Chi-Square or Fisher's exact tests were used for statistical analyses. RESULTS: We found that sCRCs tend to mutate more frequently in APC and PIK3CA genes than CACs and that mainly males were affected. Our CAC cohort identified the KRAS G12D mutation as group-specific variant that was not detected in the sCRCs. When separating conventional from non-conventional CACs, it was discovered that the conventional type shows significantly more mutations for ATM. CONCLUSIONS: Taken together, our data highlights genetic differences between sCRC and CAC and enables the possibility to utilize specific gene alterations to support the pathologist's diagnosis.
CRIS-Team Scopus Importer:2024-10-18
Keywords: Colitis-associated carcinoma; Conventional carcinoma; Mutation; Non-conventional carcinoma; Sporadic carcinoma; Ulcerative colitis